Maritime Economics & Logistics - Haralambides, Hercules E.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan.)
Maritime Economics & Logistics (MEL) is a peer-reviewed quarterly scientific publication committed to the methodological analysis of global supply chains; that is, ocean transportation, ports, marine terminals and maritime logistics. Papers are expected to be thoroughly researched, scientifically rigorous, and at the same time, of direct applicability and usefulness to practitioners and policy makers alike. All contributions are subject to strict peer-review. Often, MEL includes a special section under the heading 'Policy Perspectives'. Papers here, often solicited ones, emphasise strategic policy implications rather than scientific rigour in a strict sense. Papers in Policy Perspectives are subject to lighter peer review; this results in speedier publication. Papers submitted to MEL are submitted for both sections at the discretion of the Editors. Authors not wishing to have their papers considered for Policy Perspectives should state this in the Cover Letter.
Keywords: Business; Management science; Production management; Business logistics; Business and Management, general; Operations Management; Logistics